2012
DOI: 10.1042/bj20111579
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin binding is not a limiting step for Bacillus thuringiensis subsp. israelensis Cry4Ba toxicity to Aedes aegypti larvae

Abstract: Bacillus thuringiensis subsp. israelensis produces three Cry toxins (Cry4Aa, Cry4Ba and Cry11Aa) that are active against Aedes aegypti larvae. The identification of the rate-limiting binding steps of Cry toxins that are used for insect control in the field, such as those of B. thuringiensis subsp. israelensis, should provide targets for improving insecticides against important insect pests. Previous studies showed that Cry11Aa binds to cadherin receptor fragment CR7–11 (cadherin repeats 7–11) with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
3
31
1
Order By: Relevance
“…This conformational change is thought to cause the formation of oligomers that bind to a secondary receptor, which can be APN or ALP anchored to the membrane by a GPI anchor [6, 17]. Similarly, in Aedes mosquitoes, either Cry11Aa protoxin in the presence of BBMV or proteolytically activated Cry11Aa toxin incubated with AaeCad receptor fragment (CR7-11) alone can trigger toxin oligomerization [36, 38]. Here we also showed that C6/36 cells expressing full-length AaeCad can cause Cry11Aa oligomerization by the use of trypsin-activated Cry11Aa toxin directly or Cry11Aa protoxin in the presence of midgut juice (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This conformational change is thought to cause the formation of oligomers that bind to a secondary receptor, which can be APN or ALP anchored to the membrane by a GPI anchor [6, 17]. Similarly, in Aedes mosquitoes, either Cry11Aa protoxin in the presence of BBMV or proteolytically activated Cry11Aa toxin incubated with AaeCad receptor fragment (CR7-11) alone can trigger toxin oligomerization [36, 38]. Here we also showed that C6/36 cells expressing full-length AaeCad can cause Cry11Aa oligomerization by the use of trypsin-activated Cry11Aa toxin directly or Cry11Aa protoxin in the presence of midgut juice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although AaeCad RNAi-mediated silencing had been done in Aedes mosquitoes by dsRNA feeding [38], a transgenic Aedes mosquito line with silenced AaeCad was established in order to obtain more homogeneous animals that can be used to screen a number of other toxins. Importantly, these transgenic mosquitoes revealed a higher tolerance to Cry11Aa (about 13 fold) at LC 50 value than Aedes larvae fed AaeCad dsRNA, where only a 50% reduction in Cry11Aa toxicity was obtained compared to wild-type mosquitoes [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti (Nene et al, 2007). Previous studies investigated three ALPs as a receptor of Bti Cry toxins and found that ALP1 (AAEL009077) is a functional receptor of Cry11Aa and Cry4Ba (Fernandez et al, 2009; Rodríguez-Almazán et al, 2012). In transcriptome analysis, AAEL013330 and AAEL015070 are likely putative Cry11Aa receptors, since both of these ALPs were significantly reduced in the resistant larvae midgut.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are also present in the posterior midgut epithelial cells and/or the gastric caeca (Chen et al, 2009b; Chen et al, 2013). RNAi-mediated silencing of cadherin and of APN (AAEL012783) increased tolerance for Cry11Aa (Lee et al, 2014; Rodríguez-Almazán et al, 2012) and Cry4Ba toxicity (Saengwiman et al, 2011), respectively. These data collectively suggest that cadherins and APNs may be functionally important for Cry toxicity in mosquitoes.…”
Section: Introductionmentioning
confidence: 99%